Fire brigades - organisational assessment through excellence approach - Miguel-Oliveira, J. (2021)
Purpose - This paper aims to report the first part of a research project to understand the implementation of the Common Assessment Framework (CAF) model to assist the management of fire brigades. Design/methodology/approach - The paper involves a qualitative approach, a descriptive exploratory study that follows a case study method. The instrument used to gather empirical data was the CAF tool and involved four fire brigades. The study was anchored in the quality management literature and CAF model. Findings - The results contribute to creating knowledge about CAF's role as a useful and important tool to help fire brigades, to improve the effectiveness and efficiency of their management through the process of self-assessment and implementation of improvement initiatives. Research limitations/implications - The results need further validation in other fire departments. However, the results highlight the importance of implementing CAF to assist the management of fire brigades. Practical implications - The results encourage fire brigade organizations to introduce selfassessment with CAF. Originality/value - This investigation is a unique study, as it explores the use of CAF in fire brigades. The paper outline an analysis that does not exist in the literature, outside the scope of operational firefighting intervention, in particular the weaknesses and strengths regarding the management model, in its different domains: leadership, strategy, human resources, material resources, partnerships and process management of fire brigades.